Effectiveness of Audio-Visual on Male and Female Students’ Academic Performance in Social Studies - Esther Oluwafunmilayo Alabi; Omotayo Olabo Obielodan; Amos Ochayi Onojah; Adenike Aderogba Onojah; Ebenezer Sanya Ibironke (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Technology development in the modern era assists teachers in creating a collaborative learning environment. Despite the effectiveness of audio-visual materials in teaching and learning, there are still some hinderances in its usage. This study investigated the effects of audio-visual aids on students’ academic performance in social studies in junior secondary schools. This study is an experimental study and the sample comprised of 50 junior secondary schools. The audio-visual was in powerpoint format with concepts of marriage as material of the social studies. Students were given test questions after been taught with the Audio-visual and the results of the test are indicators of their academic performance. Analysis of the data was carried out using analysis of t-test analysis. The findings established that audio-visual aids had positive effect on students’ performance and there is no significant difference between the performance of male and female students taught using audio-visual aids. This study concluded that audio-visual method of teaching had positive effect on student's academic performance. Thus, this implies that the conventional method of teaching is less effective and performance oriented. It was however recommended that adequate supervision, monitoring and the use of audio-visual in teaching social studies by teachers of the schools should be encouraged and given adequate attention.